Processos recentes de IPO no Brasil: análise de aspectos de governança corporativa e da estrutura de propriedade - Freitas, Luciano Brito Rebouças (2014)
The process of opening up capital of a company is complex and costly but with significant benefits in terms of visibility of the company in the market as well as it diversifies the sources of funding. This study has two goals: investigate the process of IPO (IPO - Initial Public Offering) and analyze the Ownership Structure and Corporate Governance of companies that recently have gone through IPO process in Brazil. The relevance of the IPO process in a company and the effect of this process on their relationship with market suggests that a company that goes through this process is giving special attention to their corporate governance practices. On the other hand, the literature has given attention to the structure of ownership of a company that makes a public offer. In markets with high concentration of ownership this issue deserves special attention, since this feature can be negative for a successful IPO. This study as based on a sample of companies listed on the BM & FBOVESPA in the period 1995-2012, among which 122 are companies that have gone through the IPO process in 2004-2012. It was observed that companies that made IPO recently (2004-2012) are adopting good corporate governance practices. It was found that companies that opened up capital still have an Ownership Structure highly concentrated, although smaller than other companies. Moreover, it is also detected a high concentration of property after IPO process. Finally, this research analyses the identity of larger shareholders participating in recent IPO, which is characterized by a strong presence of other non-financial companies, investment funds, and families.